Rasionalitas Majelis Hakim dalam Pembatalan Akta Hibah Tanah Akibat Perbuatan Melawan Hukum oleh Ahli Waris: Studi Putusan Nomor 175/Pdt.G/2023/PN Kpn - Dewi, Eriska Desianti; Samosir, Tetti; Harlina, Indah (SIGn Jurnal Hukum, 2025)
Disputes concerning the annulment of land grant deeds between Inheritors constitute a complex issue within civil and agrarian law, requiring an in-depth understanding of the rationale behind court decisions. This research aims to analyze the rationale of the Panel of Judges of the Kepanjen District Court in Decision Number 175/Pdt.G/2023/PN Kpn regarding the annulment of Grant Deed Number 167/KEP-35.10/IX/2020. Employing a normative legal research method with a case study approach, the qualitative analysis focused on the legal considerations (ratio decidendi) within the decision. The analysis results indicate the Panel of Judges’ rationale was primarily based on the assessment of evidence corroborating the Plaintiff’s pre-grant proper claim derived from an oral transaction, setting aside the formal strength of the authentic deed due to the Defendant’s absence of rebuttal evidence. The juridical annulment of the deed was grounded in the direct application of the Nemo dat quod non habet principle, referenced through Article 210 section (2) of the Compilation of Islamic Law because the Grantor was proven to have granted part of the object that was not his right. The qualification of unlawful act against the Defendant was determined as a logical consequence of this finding, albeit without in-depth elaboration of the elements, demonstrating pragmatic reasoning. In conclusion, the judicial rationale, in this case, tends to prioritize substantive justice over formal legal certainty, yet it raises discourse concerning evidentiary standards and potential issues of inheritance law coherence that remain unaddressed.